Understanding the marital self-disclosure experience during chemotherapy for gastric cancer: a qualitative study - Ye Zhou; Ye Zhou; Chong Chin Che; Mei Chan Chong; Haiyan Zhao; Yuzhu Hou; Min Zhao (Frontiers in Psychology)
ObjectiveThis study explores the experiences of Chinese gastric cancer patients and their spouses in implementing marital self-disclosure and examines the barriers and facilitators to the acceptance of marital self-disclosure among gastric cancer patients. The study aims to assist nurses in developing effective communication strategies for patients and their spouses, thus promoting their psychological well-being.MethodsThe study employed purposive sampling with a maximum variation approach to select participants. From January to June 2024, 18 pairs of gastric cancer patients and their spouse caregivers, who were hospitalized in the oncology department of a tertiary hospital in Jingjiang, Jiangsu Province, participated in semi-structured face-to-face interviews. Data was transcribed within 24 h after each interview, supported by field notes. Directed content analysis was applied to qualitative content analysis.ResultsTraditional content analysis revealed five overarching themes and 15 sub-themes derived from the experiences of gastric cancer patients and their spouses during chemotherapy. The five themes identified were: (1) perception of marital self-disclosure, (2) the Influence of marital self-disclosure on Couples’ Well-Being, (3) addressing concerns about marital self-disclosure, (4) factors facilitating marital self-disclosure, and (5) the obstacles to marital self-disclosure.ConclusionNurses should recognize the importance of communication between spouses during chemotherapy for gastric cancer patients. Positive interventions should be adopted to alleviate one-sided, conflictual communication and avoidance behaviors. Nurses should focus on personalized communication issues, identify barriers to disclosure promptly, and provide tailored care. Furthermore, patient case management should be emphasized to facilitate the development of more effective communication strategies.